2016
DOI: 10.1016/j.jgeb.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Common variants in TCF7L2 and CDKAL1 genes and risk of type 2 diabetes mellitus in Egyptians

Abstract: In this work we studied association of common variants in transcription factor 7-like 2 (TCF7L2) and cyclin-dependent kinase 5 regulatory subunit-associated protein 1-like 1 (CDKAL1) genes with type 2 diabetes mellitus (T2DM) in Egyptians.Subjects and methodsThis is a case–control study; 180 T2DM patients and 210 control subjects were genotyped for TCF7L2 rs7903146 and rs12255372 and CDKAL1 rs7756992 single nucleotide polymorphisms (SNPs) by TaqMan method on real time polymerase chain reaction system (real tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
1
17
1
Order By: Relevance
“…[25][26][27][28]33 However, Dou et al 43 found there is no association between this SNP and T2DM in another Chinese population, which is consistent with the results in other populations. 28,39,44 In the current study, we also did not find an association between this SNP and T2DM in the Chinese population. The inconsistency was also found in the association of rs10946398 with T2DM, which was associated with T2DM in the current Chinese population, Chinese She, 45 and Russian 34 population, but not associated with T2DM in a Korean population.…”
Section: Discussioncontrasting
confidence: 77%
“…[25][26][27][28]33 However, Dou et al 43 found there is no association between this SNP and T2DM in another Chinese population, which is consistent with the results in other populations. 28,39,44 In the current study, we also did not find an association between this SNP and T2DM in the Chinese population. The inconsistency was also found in the association of rs10946398 with T2DM, which was associated with T2DM in the current Chinese population, Chinese She, 45 and Russian 34 population, but not associated with T2DM in a Korean population.…”
Section: Discussioncontrasting
confidence: 77%
“…COL8A1 , KCNQ1 , ALX4 , and HNF1 . TCF7L2 was the most widely reported gene in the region, in countries that include Palestine[ 54 ], Lebanon[ 55 ], UAE[ 56 ], Egypt[ 57 ], Qatar[ 58 ], and Tunisia[ 59 ]. In the Lebanese population, associations with T2D have been found with variants of the COL8A1 , KCNQ1 , ALX4 , and HNF1 genes[ 60 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…CDKAL1 gene is located on chromosome 6p22.3 and encodes a 65-kD protein CDKAL1 which may be involved in beta cell dysfunction and T2DM susceptibility [14]. Evidence of this protein functioning also as a tRNA modification enzyme has been shown in some recent studies and activity of which is associated with ATP generation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%